Pengaruh Diferensiasi Produk, Strategi Harga, dan Saluran Distribusi terhadap Daya Saing Produk Vaseline di Kalangan Mahasiswa di Palangkaraya - Bintang Ramadhan; Elisa Pirda Sari; Julira Julira; Meitrisia Meitrisia; Ria Amelia; Tasya Roswita; Serly Sapitri (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the influence of product differentiation, pricing strategy, and distribution channels on the competitiveness of Vaseline products among university students in Palangkaraya. The research adopts a quantitative approach using a survey method, with data collected through questionnaires distributed to 100 student respondents. Data analysis was conducted using the Partial Least Squares (PLS) method with the assistance of SmartPLS 3.0 software. The findings indicate that product differentiation, pricing strategy, and distribution channels have a positive and significant impact on product competitiveness. These results suggest that an integrated and consumer-oriented marketing strategy is key to enhancing Vaseline's competitive position within the student market segment.